Multisensory integration: maintaining the perception of synchrony. - Spence, C; Squire, S (2003)
We are rarely aware of differences in the arrival time of inputs to each of our senses. New research suggests that this is explained by a 'moveable window' for multisensory integration and by a 'temporal ventriloquism' effect.